SOURCE STUDIES OF THE HISTORY OF EDUCATION IN THE "SECOND MUSLIM RENAISSANCE" PERIOD (XIV – XVI CENTURIES) (World Bulletin of Management and Law, 2023)
The historical period called the "Second Muslim Renaissance" coincides with the reign of Amir Temur and the Timurids, occupying a key place in the centuries-old history of the Uzbek people, and is considered an important turning point in historical reality. There are many sources about the Timurid period. Although this period is approached differently in the sources, the processes of socio-political, economic and cultural development are reflected. The works of Ghiyosiddin Ali, Abdurazzaq Samarkandi, Nizamiddin Shami, Sharafiddin Ali Yazdi, Muhammad Khavafi, Ibn Arabshah, Mirza Ulugbek, Ghiyosiddin Koshi, Zahiriddin Muhammad Babur, Alisher Navoi, Khondamir, Mirzo Muhammad Haidar and other historical scholars have reached our time. This article provides valuable information about the source studies of the History of Maarif during the time of Amir Temur and Mirzo Ulugbek